2020
DOI: 10.1101/2020.06.13.145029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory aversion in absolute pitch possessors

Abstract: Absolute pitch (AP) refers to the ability of identifying the pitch of a given tone without reliance on any reference pitch. The downside of possessing AP may be the experience of disturbance when exposed to out-of-tune tones. Here, we investigated this so-far unexplored phenomenon in AP, which we refer to as auditory aversion. Electroencephalography (EEG) was recorded in a sample of AP possessors and matched control musicians without AP while letting them perform a task underlying a so-called affective priming… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(90 reference statements)
2
1
0
Order By: Relevance
“…By contrast, the control participants showed no variation in the RT as a function of the matching condition. In line with previous Stroop and other interference studies on AP, 25,44,47,49–52,80 these results confirm that the pitch‐labeling process is largely nonsuppressible when triggered by tone exposure, interfering with the conflicting task of sight‐reading. The fact that our matched control musician sample without AP did not show this interference pattern further suggests that automaticity in the context of pitch labeling is unique for AP.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, the control participants showed no variation in the RT as a function of the matching condition. In line with previous Stroop and other interference studies on AP, 25,44,47,49–52,80 these results confirm that the pitch‐labeling process is largely nonsuppressible when triggered by tone exposure, interfering with the conflicting task of sight‐reading. The fact that our matched control musician sample without AP did not show this interference pattern further suggests that automaticity in the context of pitch labeling is unique for AP.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous Stroop and other interference studies on AP [22,40,43,[45][46][47][48]73], these results confirm that the pitch-labeling process is largely non-suppressible when triggered by tone exposure, interfering with the conflicting task of sight-reading. The fact that our well-matched control musician sample without AP did not show this interference pattern further suggests that automaticity in the context of pitch labeling is unique for AP.…”
Section: Stroop and Tdcs Findingssupporting
confidence: 90%
“…If pitch labeling is difficult to suppress, AP musicians are expected to show some signs of increased inhibitory load due to the conflicting information, such as more commission errors and/or larger N2d/P3d amplitudes than non-AP musicians. Also, it has been suggested that AP musicians may have an aversion towards mistuned tones (Levitin and Rogers, 2005 ; Rogenmoser et al, 2020 ). This could increase the inhibitory load even further.…”
Section: Introductionmentioning
confidence: 99%